Bidirectional effects of oral anticoagulants on gut microbiota in patients with atrial fibrillation - Li, Wan; Li, Changxia; Ren, Cheng; Zhou, Shiju; Cheng, Huan; Chen, Yuanrong; Han, Xiaowei; Zhong, Yiming; Zhou, Licheng; Xie, Dongming; Liu, Haiyue; Xie, Jiahe (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Unbalanced gut microbiota is associated with a higher risk of thrombosis in patients with atrial fibrillation (AF). Oral anticoagulants (OACs) have been found to significantly reduce the risk of thromboembolism and increase the risk of bleeding. However, the OAC-induced alterations in gut microbiota in patients with AF remain elusive. Methods: In this study, the microbial composition in 42 AF patients who received long-term OAC treatment (AF-OAC group), 47 AF patients who did not (AF group), and 40 volunteers with the risk of AF (Control group) were analyzed by 16S rRNA gene sequencing of fecal bacterial DNA. Metagenomic functional prediction of major bacterial taxa was performed using the Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt) software package. Results: The gut microbiota differed between the the AF-OAC and AF patients. The abundance of the Bifidobacterium and Lactobacillus decreased in the two diaease groups at the genus level, but OACs treatment mitigated the decreasing tendency and increased beneficial bacterial genera, such as genus Megamonas. In addition, OACs reduced pro-inflammatory taxa on the genus Ruminococcus but increased certain potential pathogenic taxa, such as genera Streptococcus, Escherichia-Shigella, and Klebsiella. Subgroup LEfSe analyses revealed that Bacteroidetes, Brucella and Ochrobactrum were more abundant in the anticoagulated bleeding AF patients, Akkermansia and Faecalibacterium were more abundant in the non-anticoagulated bleeding AF patients. The neutrophil to lymphocyte ratio (NLR) of the AF and the AF-OAC groups was higher than that of the control group, but compared with the AF group, it was lower in the AF-OAC group (p < 0.05). Ruminococcus was positively correlated with the NLR and negatively correlated with the CHA2DS2-VASc score (p < 0.05). Conclusions: Our study suggests that OACs may benefit AF patients by reducing the inflammatory response and modulating the composition and abundance of gut microbiota. In particular, OACs increase gut microbiota involved in bleeding and gastrointestinal dysfunction, which indicates exogenous supplementation with Faecalibacterium and Akkermansia may be a prophylactic strategy for AF-OAC patients to lower the risk of bleeding after anticoagulation.